Peran Dewan Pengawas Syariah dalam Pengawasan di Bank Syariah (Studi Kasus Bank Sumut Syariah Kecamatan Tebing Tinggi) - Panjaitan, Arnita Septiani; Jannah, Nurul (Regress: Journal of Economics & Management, 2022)
Supervisory Journal is part of the management function. Supervision is the process of ensuring that organizational and management objectives are achieved. Functionally, there are many names for control, such as evaluating, assessing, and correcting. It's just that controlling is used more because it contains connotations that include setting standards, measuring activities, and taking corrective actions that are not objective. The supervisory body is also independent, in the sense that its work is not related or influenced by other parties, both internal and external to the company. Thus, the assessment carried out is expected to be objective so that an evaluation can be carried out for changes for the better. This research is a research based on a conceptual study. By only using secondary data obtained from: journals, books and writing materials related to the theme of this research, the Sharia Supervisory Board (DPS) is an independent body placed by the National Sharia Council (DSN) in Islamic financial and banking institutions. To ensure the effectiveness of DPS performance Apart from being seen from the performance of their duties, the effectiveness of DPS members must consist of carrying out their duties as supervisors and must be independent, without influence from any party, both from the bank and from parties other than the bank.